2021
DOI: 10.1111/sji.13095
|View full text |Cite
|
Sign up to set email alerts
|

Association of reduced maternal sHLA‐G5 isoform levels and elevated TNF‐α/IL‐4 cytokine ratio with Recurrent Pregnancy Loss: A study on South Indian women

Abstract: Inflammation is of critical importance in successful implantation during pregnancy.However, the establishment of maternal immune tolerance towards semi-allograft foetus is more exigent and is achieved predominantly by human leukocyte antigen-G (HLA-G) isoforms with a special emphasis on soluble HLA-G5 (sHLA-G5).Constant inflammation and lack of resolution by anti-inflammatory milieu, due to aberrant expression of critical immunoregulatory molecules such as sHLA-G5 and dysfunctional T helper cells 1 and 2 (Th1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Five studies reported sHLA‐G levels in women with RM as compared with controls, including three studies that considered the differences during pregnancy, 30–32 and two that focused on non‐pregnant women 12,33 . One targeted only the sHLA‐G5 isoform 31 . The meta‐analysis showed that these five articles had markedly significant heterogeneity ( p = .001, I 2 = 98.0%) and no significant difference were found using the random‐effects model (standardized mean difference [SMD] −1.119, 95% confidence interval [CI] −2.422, 0.815; z = 1.68, p = .093; total 676 women; Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies reported sHLA‐G levels in women with RM as compared with controls, including three studies that considered the differences during pregnancy, 30–32 and two that focused on non‐pregnant women 12,33 . One targeted only the sHLA‐G5 isoform 31 . The meta‐analysis showed that these five articles had markedly significant heterogeneity ( p = .001, I 2 = 98.0%) and no significant difference were found using the random‐effects model (standardized mean difference [SMD] −1.119, 95% confidence interval [CI] −2.422, 0.815; z = 1.68, p = .093; total 676 women; Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…12,33 One targeted only the sHLA-G5 isoform. 31 The metaanalysis showed that these five articles had markedly significant heterogeneity (p = .001, I 2 = 98.0%) and no significant difference were found using the random-effects model (standardized mean difference…”
Section: Meta-analysis: Shla-g Level and Rmmentioning
confidence: 94%
See 1 more Smart Citation
“…This also includes the production of a glycoprotein molecule HLA‐G, derived from placenta flooding maternal‐fetal interface and in maternal circulation throughout the pregnancy 15,57 . Immunologically a successful pregnancy can be divided into alternate phases of pro (1 st and 3 rd ) and anti‐inflammation (2 nd ) for implantation, parturition and for fetal growth respectively, 58 This immunological shift during gestation is mediated by HLA‐G 47 . HLA‐G works via various mechanisms like it induces tolerogenic dendritic cells (DC‐10) and other regulatory cells via interaction with ILT‐2 and/or ILT‐4 receptor to produce anti‐inflammatory cytokine like interleukin‐10 59 .…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of inflammatory cytokines (such as TNF-α) in RSA patients compared to controls has been reported, indicating the potential underlying mechanism of these cytokines in RSA pathogenesis. 18,19 Recently, TNFi has been indicated in treating RSA patients for rescuing pregnancy management, while these findings are conflicting.…”
Section: Discussionmentioning
confidence: 99%